The paucity of high-level evidence for therapy in pediatric cardiology - Emily Littman; Diana Hsiao; Kanekal S Gautham (Wolters Kluwer Medknow Publications, 2023)
Introduction : Clinical practice should be based on the highest quality of evidence available. Therefore, we aimed to classify publications in the field of pediatric cardiology in the year 2021 based on the level of scientific evidence. Materials and Methods: A PubMed search was performed to identify pediatric cardiology articles published in the calendar year 2021. The abstract or manuscript of each study was reviewed. Each study was categorized as high, medium, or low level of evidence based on the study design. Disease investigated, treatment studied, and country of publication were recorded. Randomized control trials (RCTs) in similar fields of neonatology and adult cardiology were identified for comparison. Descriptive statistics were performed on the level of evidence, type of disease, country of publication, and therapeutic intervention. Results : In 2021, 731 studies were identified. A decrease in prevalence for the level of evidence as a function of low, medium, and high was found (50.1%, 44.2%, and 5.8%, respectively). A low level of evidence studies was the majority for all types of cardiac disease identified, including acquired heart disease, arrhythmias, congenital heart disease, and heart failure, and for treatment modalities, including circulatory support, defibrillator, percutaneous intervention, medicine, and surgery. In a subgroup analysis, most high-level evidence studies were from the USA (31%), followed by China (26.2%) and India (14.3%). Comparing RCTs, 21 RCTs were identified in pediatric cardiology compared to 178 in neonatology and 413 in adult ischemic heart disease. Conclusions : There is a great need for the conduct of studies that offer a high level of evidence in the discipline of pediatric cardiology.